E-Wallet and Its Prospects and Challenges: Small Industry Operators in Alor Setar, Kedah - Nur Bahirah Husna Mohtar; Muhammad Aunurrochim Mas'ad Saleh (USIM Press, 2024)
This paper is to study the prospects and challenges using e-wallets among small industry located at Alor Setar, Kedah which has a great potential in agriculture, tourism and economic development sectors which have increased rapidly in recent years. The objective of this study is to explain transactions using e-wallets in Malaysia whether it comply with Sharia guidelines as well as explaining whether the e-wallets apps, is user-friendly which may improve the small industry operator in order to get a reasonable profit and blessing by using an e-wallet that complies with Sharia. Nevertheless the use of e-wallets (Islamic) is still low among them. The methodology used is quantitative studies and qualitative studies. The questionnaire is distributed online via Google Form among 100 respondents who live around Alor Setar.